2018
DOI: 10.1007/s00726-018-2546-2
|View full text |Cite
|
Sign up to set email alerts
|

New aspects of antiproliferative activity of 4-hydroxybenzyl isothiocyanate, a natural H2S-donor

Abstract: The effect of 4-hydroxybenzyl isothiocyanate (HBITC), a natural H2S-donor from white mustard seeds (Sinapis alba), on the proliferation of human neuroblastoma (SH-SY5Y) and glioblastoma (U87MG) cells was studied and some aspects of the mechanism of its activity were suggested. The inhibition of both SH-SY5Y and U87MG cell proliferation was associated with an increase in the thiosulfate level, the number of cells with the inactive form of Bcl-2 protein, and with a decrease of mitochondrial membrane potential. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 49 publications
(60 reference statements)
0
6
0
Order By: Relevance
“…p -hydroxybenzyl ITC is currently obtained by enzymatic hydrolysis of sinalbin, a major glucosinolate found in the seeds of white mustard, Sinapis alba . Considering the recognized biological properties of that ITC [ 35 , 36 ] together with its marked instability in aqueous media [ 37 ], it would be advisable to further investigate the properties of its CD-inclusion complex with regard to solubility, stability and bioavailability.…”
Section: Resultsmentioning
confidence: 99%
“…p -hydroxybenzyl ITC is currently obtained by enzymatic hydrolysis of sinalbin, a major glucosinolate found in the seeds of white mustard, Sinapis alba . Considering the recognized biological properties of that ITC [ 35 , 36 ] together with its marked instability in aqueous media [ 37 ], it would be advisable to further investigate the properties of its CD-inclusion complex with regard to solubility, stability and bioavailability.…”
Section: Resultsmentioning
confidence: 99%
“…Benzyl ITC has been previously found to display anti-proliferative, anti-cancer and anti-metastatic properties [53]. Jurkowska et al (2018) reported that 4-hydroxybenzyl ITC from white mustard seeds possesses an anti-proliferative effect on human neuroblastoma (SH-SY5Y) and glioblastoma (U87MG) [54]. These implied that M1S9 could potentially demonstrate anti-tumor activity with the presence of benzyl ITC and 4-hydroxybenzyl ITC, and its underlying mechanism remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…The activity of TST and MPST is increased after garlic-derived diallyl trisulfide (DATS) treatment [ 206 ]; moreover, N-acetyl-L-cysteine increases the MPST activity [ 207 ]. On the other hand, the level of TST and MPST proteins in the mitochondria is decreased after 4-hydroxybenzyl isothiocyanate (HBITC) (H 2 S donor) treatment [ 208 ]. The activity of all these factors is associated with the TST antioxidative activity [ 202 ].…”
Section: Sulfurtransferasesmentioning
confidence: 99%
“…Nagahara showed that reactive oxygen species could oxidize the catalytic site Cys 247 of MPST (Cys–SO − , Cys–SO 2− and Cys–SO 3− ) and that the MPST activity decreased under oxidizing conditions and increased under reducing conditions [ 220 ]. Our previous studies [ 208 ] have demonstrated that the increased H 2 S and thiosulfate levels in HBITC-treated SH-SY5Y cells have been associated with downregulation of the level of TST and MPST, which suggest that the sulfhydryl groups of these enzymes can be modified by S-sulfuration (-SH to -SSH), or by oxidative stress (-SH to -SOH).…”
Section: Sulfurtransferasesmentioning
confidence: 99%